2002
DOI: 10.1038/sj.bjp.0704821
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase‐2 inhibition increases blood pressure in rats

Abstract: 1 It is known that nonselective cyclo-oxygenase (COX) inhibitors have small but signi®cant eects on blood pressure (BP), most notably in hypertensive patients on antihypertensive medication. Whether selective COX-2 inhibitors also interfere with BP regulation is not well understood. Therefore, we aimed to examine the eect of chronic treatment with a selective COX-2 inhibitor (rofecoxib) on systolic blood pressure (sBP) in normotensive Wistar-Kyoto rats (WKY) and on the developmental changes of sBP in young spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
43
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 55 publications
8
43
1
1
Order By: Relevance
“…The differential effects of celecoxib and rofecoxib on blood pressure in the study from Hermann et al are consistent with previous animal studies in rodent models of hypertension 17,18 and also parallel clinical findings seen in elderly patients treated with the different COX-2-selective inhibitors. 19 Although celecoxib attenuated further increases in systolic blood pressure (SBP) in week 8 compared with the other treatment groups, the difference in mean SBP was still small (9 to 12 mm Hg) relative to the severe hypertension (mean SBP Ͼ200 mm Hg) found in these Dahl salt-sensitive animals.…”
supporting
confidence: 88%
“…The differential effects of celecoxib and rofecoxib on blood pressure in the study from Hermann et al are consistent with previous animal studies in rodent models of hypertension 17,18 and also parallel clinical findings seen in elderly patients treated with the different COX-2-selective inhibitors. 19 Although celecoxib attenuated further increases in systolic blood pressure (SBP) in week 8 compared with the other treatment groups, the difference in mean SBP was still small (9 to 12 mm Hg) relative to the severe hypertension (mean SBP Ͼ200 mm Hg) found in these Dahl salt-sensitive animals.…”
supporting
confidence: 88%
“…The previous case report in 2002 clearly demonstrated that sCOX-2 inhibitors caused acute tubulointerstitial nephritis (ATIN). 2 Moreover, other studies 9 have revealed that sCOX-2 inhibitors also caused acute ischemic tubular necrosis, nephrotic syndrome due to minimal change disease, acute papillary necrosis, 1,10 hyperkalemia, and type 4 renal tubular acidosis. The previous study showed that conventional NSAIDs increased the risk of renal progression and end-stage renal disease in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent clinical study has also provided evidence that COX-2 inhibitors affect renal hemodynamics. 9 Acute kidney injury caused by sCOX-2 inhibitors was encountered several days after starting drug use. The previous case report in 2002 clearly demonstrated that sCOX-2 inhibitors caused acute tubulointerstitial nephritis (ATIN).…”
Section: Discussionmentioning
confidence: 99%
“…Rofecoxib significantly elevated systolic BP (SBP) in SHR or WKY rats with normal-salt or high-salt diet, but not in rats on low-salt intake, which suggested that the hypertension induced by COX-2 inhibition can occur independently of a genetic predisposition to hypertension and can be prevented by salt deprivation. 50 In mice COX-2 inhibition enhanced the pressure effect of angiotensin II. 31 In double-blind, randomized, controlled, clinical trials, conflicting results have been obtained about the influence of COX-2 inhibitor treatment on BP.…”
Section: Cox-2 Inhibitors and Hypertensionmentioning
confidence: 99%